PRIMARY ANTIBIOTIC RESISTANCE AND EFFECTIVENESS OF CLARITHROMYCIN VS METRONIDAZOLE BASED THERAPY FOR HELICOBACTER PYLORI INFECTION IN CHILDREN - Salman, Nadia; Nighat Haider,; Muqaddar Shah,; Rehmana Waris,; Maryum Naseer,; Ayesha Razzaq,; Jai Krishin, (Journal of Ayub Medical College Abbottabad, 2023)
Background: NASPGHAN guidelines recommend regional antibiotic susceptibility profiling for H. pylori eradication treatment. Profiling local antibiotic resistance patterns is mandatory for successful H. pylori eradication in children. The aim of our study was to determine primary resistance to Clarithromycin and Metronidazole, most commonly used in the eradication regimens in children presenting with symptomatic H. pylori infection. This study was conducted at Children Hospital PIMS Islamabad from June 2020 to August 2021. Methods: The children of either gender age 2-14 years having symptomatic H. pylori infection (hematemesis, chronic abdominal pain) underwent stool for H. pylori Antigen. Children requiring urgent diagnostic endoscopy underwent rapid urease tests. Biopsies were taken from children having positive stool H.pylori Ag and rapid urease test for histological examination. The biopsy specimens were cultured and subsequently tested for antibiotic sensitivity. Results: Out of 54 children having H. pylori infection 40/54 (74.074%) children had strains susceptible to antimicrobials and 14/54 (25.92%) were having resistance to antimicrobials. According to the pattern of antimicrobial sensitivity, they were further grouped into three (a) Clarithromycin and Metronidazole sensitive group (18/40, 45%) (b) Clarithromycin sensitive and Metronidazole resistant group (12/40, 30%) (c) Metronidazole sensitive group (10/40 25%). Conclusion: Clarithromycin and Metronidazole cannot be used as1stline treatment for H. pylori eradication in children and can only be used with known antimicrobial susceptibility.